1987
DOI: 10.2172/6533484
|View full text |Cite
|
Sign up to set email alerts
|

Methodology and assumptions for evaluating heating and cooling energy requirements in new single-family residential buildings: Technical support document for the PEAR (Program for Energy Analysis of Residences) microcomputer program

Abstract: This is a Library Circulating Copy which may be borrowed for two weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Envelope characteristics were taken from two primary surveys of existing housing characteristics for homes built after 1979 (Huang et al 1987(Huang et al , 1999 Huang et al (1987Huang et al ( , 1999.…”
Section: Homes Relying On Infiltration Alonementioning
confidence: 99%
“…Envelope characteristics were taken from two primary surveys of existing housing characteristics for homes built after 1979 (Huang et al 1987(Huang et al , 1999 Huang et al (1987Huang et al ( , 1999.…”
Section: Homes Relying On Infiltration Alonementioning
confidence: 99%
“…After the retrofits, only the gas-fired ranges and ovens remain. One published value for gas use in ranges and ovens is 60 therms per year (Huang et al 1987). The Energy Information Administration, on the other hand, reports a national average of 77 therms per year, but this includes other appliances such as clothes dryers, outdoor gas grills, hot tubs, etc.…”
Section: Natural Gas Savingsmentioning
confidence: 99%
“…For the residential sites, the magnitude of the internal loads from appliances and lighting are estimated from the minimum monthly electricity consumption over the previous 16 months. Previous LBL work has shown that approximately 75% of typical residential electricity usage is input to the conditioned space as sensible heat gains and 10% is input as latent gains (Huang et al, 1987), with the remaining 15% occurring outside of the conditioned space. Occupant internal gains .are based on the number of occupants per house as reported in the site surveys as well as previous work , ASHRAE, 1989.…”
Section: Building Geometry and Adjoining Surfacesmentioning
confidence: 99%
“…3. Attic ventilation rates, which are important for determining attic temperature, are typically unknown and vary a great deal from house to house (Huang et al, 1987 Given the importance of the duct system in the cooling energy use of a building, the impact of a high-albedo roof on cooling energy will be inore than just for the change in conductive loads. With ducts in the attic space, the higher albedo roof will both reduce the cooling load on the conditioned space and increase the cooling system efficiency.…”
mentioning
confidence: 99%